Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

Sequestration of antimony(V) and carbon by secondary iron (oxyhydr)oxides during ferrihydrite organominerals transformation: A nanoscale study and molecular mechanisms - Yiqing Wang; Mengchang He; Chenfei Zhang; Chunye Lin; Wei Ouyang; Xitao Liu (Chemical Geology, 2026)

Cigarette smoking combines with genetic variants to regulate FOXN3 and associate with bladder cancer risk - Yiwen Zheng; Youhan Wu; Jinyue Zhang; Chenfei Zhao; Tianqin Wang; Qunbo Wang; Qiang Lv; Chao Qin; Lin Yuan; Haiyan Chu; Mulong Du; Meilin Wang; et al. (Archives of Toxicology, 2026)

Why Super Typhoon Occurrence Over the Western North Pacific Ocean Tends to be More in Autumn Than Summer - Zhiming Feng; Xiuping Yao; Chenfei Liao; Jiali Ma; Ning Pan; Yanluan Lin (International Journal of Climatology, 2025)
Based on the tropical cyclone (TC) best‐track datasets from the China Meteorological Administration during 1949–2020 and the fifth generation ECMWF atmospheric reanalysis (ERA5) datasets, we investigate the characteristics of super typhoons (SuperTYs) over the western North Pacific (WNP) and associated mechanism in this study. The results show that SuperTYs are prone to occur in autumn over the WNP, nearly 30% of the autumn TCs develop into SuperTYs, and autumn SuperTYs account for more than half of the annual total. This is due to both favourable oceanic and atmospheric conditions. In southeastern WNP, the sea surface temperature (SST) in autumn is higher than that in summer, inducing zonal circulation anomalies and enhancing low‐level westerlies. Consequently, the monsoon trough strengthens and extends eastward, favouring enhanced autumn typhoon occurrence in the southeastern WNP. This southeastward shift facilitates TCs to remain over the warm ocean for a longer period and makes them more prone to develop into SuperTYs. Furthermore, TCs tend to take westward‐moving tracks in autumn due to stronger easterly steering flows compared with summer, resulting in more TCs passing over the South China Sea (SCS) to the east of the Philippines where the vertical wind shear (VWS) is relatively weaker and prone to develop into superTYs.

Impact of urban landscape patterns on butterfly diversity in Fuzhou City parks - Ying Lin; Shanjun Huang; Wenqiang Fang; Yaling Huang; Chenfei Gao; Yankai Huang; Ruoxian Zheng; Weicong Fu (Science of The Total Environment, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Strategic small molecule engineering: Unleashing the full potential of Kevlar aramid membrane in organic solvent nanofiltration - Yanqing Xu; Jiaqi Xiong; Qite Qiu; Chenfei Lin; Junbin Liao; Huiming Ruan; Jiangnan Shen (Chemical Engineering Journal, 2024)

The microclimate impact of treetop walk based on plant community simulation - Ying Lin; Shanjun Huang; Han Xu; Wenqiang Fang; Chenfei Gao; Jingkai Huang; Weicong Fu (Environmental Science and Pollution Research, 2024)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Morphological and physicochemical characteristics, biological functions, and biomedical applications of diatom frustule - Chenfei Yang; Chao Feng; Yuhang Li; Zheng Cao; Yan Sun; Xiaohui Li; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2023)